Stock reverberation due to international trade related economic factors - Jeyalakshmi, R.; Suresh, R.; Prabaharan, T.; Keerthana, B. (University of Jaffna, 2024)
The economic activities of a nation are measured through various macroeconomic factors such as GDP, EXIM rate, unemployment level, Wholesale Price Index (WPI), and Consumer Price Index (CPI). Numerous studies have focused on identifying the association between inflation and stock prices, with some also highlighting the relationship between gold prices and stock price volatility. This study uses exchange rate and balance of trade as indicators to predict stock price volatility in China. The stock price volatility is measured using the Shanghai Stock Exchange Composite Index (SSE Composite Index). An analytical method is employed to evaluate the involved variables, with Johansen integration used to determine the relationships between them. The Vector Error Correction Model (VECM) is utilized to model these relationships. The Granger causality test and Johansen co-integration test measure the causal relationships of economic variables on the stock market indices. The findings indicate that the exchange rate positively influences stock prices, whereas the balance of trade shows a negative relationship. The exchange rate Granger-causes stock prices, but the reverse is not true. A similar Granger-causing relationship exists between the balance of trade and stock prices. The study also reveals that while the exchange rate of RMB to USD may not have a strong impact on stock prices, the exchange rates of other currencies may significantly influence China's stock prices.
Keywords: Balance of Trade; Exchange Rate; Granger Causality; Nifty; Volatility